PENGARUH KONSENTRASI Indole Butryc Acid (IBA) DAN MEDIA TANAM TERHADAP PERTUMBUHAN STEK BATANG ANGGUR (Vitis vinifera L.) - Handayani, Nur Safira; Karno, Karno; Rosyida, Rosyida (JURNAL AGROTROPIKA, 2025)
The aim of this study is to examine the influence of Indole Butyric Acid (IBA) concentration and planting media on the growth of grapevine cuttings (Vitis vinifera L.). The research was conducted from September to November 2023 at the Greenhouse Block E, Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang. The treatments were arranged in a factorial design (4x3) using a completely randomized design with three replications. The first factor was IBA concentration with four treatments: 0 ppm (Control), 1000 ppm), 2000 ppm), and 3000 ppm. The second factor was planting media with three treatments: soil:sand (1:1), soil:sand husk charcoal (1:1:1), and soil:sand (1:1). The observation variables included the time of shoot emergence, shoot length, number of leaves, number of roots, root length, and root volume. The observation data were analyzed using analysis of variance (ANOVA) and further tested with Duncan's Multiple Range Test (DMRT) at a 5% significance level. The results showed that the 3000 ppm IBA concentration treatment had a significantly higher effect compared to the 0 ppm, 1000 ppm, and 2000 ppm concentrations on the parameters of shoot emergence time, shoot length, number of leaves, number of roots, and root volume. The planting media treatment had a significant effect on the parameters of shoot emergence and shoot length. The soil:sand media was the most effective for the shoot length parameter. There was a significant interaction between IBA concentration treatment and planting media on the parameters of shoot length, number of leaves, and root length. The conclusion of this study is that the 3000 ppm IBA concentration had the best effect on all parameters. The soil:sand planting media had the best effect on shoot length, number of leaves, and root volume. The 3000 ppm IBA concentration in the soil:sand planting media was the most effective for shoot length and number of leaves.